DIGITAL TRANSFORMATION OF EDUCATION: IMPROVING STUDENTS CRITICAL REASONING SKILLS IN SOCIAL MEDIA-BASED DANCE LEARNING - Shalsa Khoiru Nisa; Ayo Sunaryo (Universitas Pendidikan Indonesia, 2024)
This study aims to determine whether social media-based dance learning can improve critical reasoning skills of class X IPS 3 students at SMA Pasundan 2 Bandung or not. This study uses a quantitative approach with the One Group Pre-test Post-test Design experimental method, with sampling using a non-probability sampling technique of the Purposive Sampling type which is taken through consideration. Data collection for this study uses observation, interviews, tests, literature studies, and documentation, which are analyzed using IBM SPSS Statistic Ver.26 software. The results of this study indicate that social media-based learning is quite effective in improving critical reasoning skills of class X IPS 3 students at SMA Pasundan 2 Bandung as indicated by the percentage increase in pre-test and post-test scores of 31% with an average pre-test score of 53 while the post-test score is 84. Based on this, the application of social media as a learning medium in dance learning can be an innovation and reference for teachers, especially art and culture teachers and teachers from other scientific fields to collaborate social media in learning in order to achieve the desired learning goals.